Comparison of the electroanalytical performance of chemically modified graphenes (CMGs) using uric acid - Chee, Sze Yin (2013)
We compared the differential pulse voltammetric performance of various chemically modified graphenes (CMGs) to those of glassy carbon (GC) and edge plane pyrolytic graphite (EPPG), using a biologically important analyte, uric acid. Analytical parameters of sensitivity, linearity, repeatability and selectivity were considered. Graphite oxide, graphene oxide, chemically reduced graphene oxide, electrochemically reduced graphene oxide and thermally reduced graphene oxide (TR-GO) were studied. TR-GO showed the highest sensitivity and selectivity, but among the poorest linearity and reproducibility. The other CMGs generally demonstrated more sensitive but less selective and reproducible responses than GC and EPPG. These results will enhance our understanding of the applicability of CMGs in biosensing.